Burden-sharing or migration management? - Mathias Czaika; Amy Mayer (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
This paper analyses the impact of refugee movements on emergency and development aid allocation decisions of bilateral donors in a political economic framework. We investigate two alternative hypotheses about donor motivations: first, an altruistic burden-sharing policy towards recipient countries that serve as hosts for a significant refugee population, and second, a more self-interested migration prevention policy focusing on recipient countries that actually cause refugee movements. We find some evidence that short-term humanitarian aid is predominantly used for burden-sharing purposes towards major refugee havens, while long-term development assistance is rather allocated to the source countries either to prevent further refugee outflows or to facilitate voluntary repatriation. Furthermore, it is evident that the inflow of asylum seekers into donor countries leads to a reallocation of aid funds to the respective countries of origin.
Keywords: F22; J61; H77; 330; Refugee burden-sharing; migration prevention; aid allocation